2020
DOI: 10.1080/15387216.2020.1822751
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing labor intensity in agriculture and the accessibility of major cities shape the rural population decline in postsocialist Russia

Abstract: Rural population decline has been observed in most developed and emerging economies but has been especially apparent in postsocialist countries. In this paper, we investigate the spatial patterns and the determinants of the rural population dynamics during the transition period from 1991 to 2010 in Tyumen Province, Russia, with the aim of better understanding the forces underlying depopulation. We use descriptive and exploratory statistical tools to analyze data from population censuses and district-level stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
1
3
0
1
Order By: Relevance
“…Explaining the spatial pattern of steppe restoration In general, steppe has persisted or has been restored in areas further away from infrastructure (roads, settlements), in areas with complex terrain and areas with harsh climatic conditions. This is in line with other studies that showed that human drivers such as a shrinking and ageing population and the great distances between markets and settlements are highly relevant (Rey Benayas 2007;van Vliet et al 2015;Sheludkov et al 2020). The positive relationship between crop abandonment and remoteness from settlements and infrastructure has also been found across Russia, Ukraine and Kazakhstan (Meyfroidt et al 2016), as well as in the neighbouring states of Western Siberia (Nguyen et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Explaining the spatial pattern of steppe restoration In general, steppe has persisted or has been restored in areas further away from infrastructure (roads, settlements), in areas with complex terrain and areas with harsh climatic conditions. This is in line with other studies that showed that human drivers such as a shrinking and ageing population and the great distances between markets and settlements are highly relevant (Rey Benayas 2007;van Vliet et al 2015;Sheludkov et al 2020). The positive relationship between crop abandonment and remoteness from settlements and infrastructure has also been found across Russia, Ukraine and Kazakhstan (Meyfroidt et al 2016), as well as in the neighbouring states of Western Siberia (Nguyen et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Viabilizar o acesso a serviços públicos, como nas áreas da educação e saúde, é fundamental para evitar as limitações que condicionam a exclusão social e a necessidade de mobilidade (Camarero e Oliva, 2019). A falta de serviços locais sujeita as pessoas à deslocação para cidades ou para núcleos urbanos maiores de forma a satisfazer as necessidades sociais e económicas (Sheludkov et al, 2020). Da mesma forma, a possibilidade de promover a fixação de jovens locais bem como a transição de jovens oriundos do meio urbano depende da disponibilidade de serviços básicos e da melhoria de acesso à internet, condições que podem potencializar a revitalização local e o desenvolvimento de atividades não agrícolas (Mickovic et al, 2020), como também fortalecer a agricultura e a pecuária, atividades vistas como alternativa de desenvolvimento de regiões periféricas (Kołoszko-Chomentowska e Zdziarstek, 2019).…”
Section: Discussionunclassified
“…Inadequate economic reforms and a crisis between 1991 and 1994 worsened the financial situation, job market, and labor force. The loss of industrial and agricultural sectors, which were productive during Soviet times, had a devastating impact on employment and job availability in both urban and rural areas (Sheludkov, Kamp, and Müller 2021). As a result, the lack of social and economic support from the Moldovan authorities led to a significant increase in regular and irregular labor migration (Cuc, Lundback, and Ruggiero 2006; Hönekopp et al 2008; Pinger 2010; Burdelnii et al 2012; Ratzmann 2012; Birca 2015).…”
Section: Contextualizing Moldovan Migration In Eastern Europementioning
confidence: 99%